Effect of delignification and bleaching stages on cellulose purity of oil palm empty fruit bunches - Susi, S.; Ainuri, M.; Wagiman, W.; Falah, M. A. F. (2022)
Oil palm empty fruit bunches (OPEFB) have not been properly utilized by most palm oil mills and communities in Indonesia. The processing and utilization of OPEFB by palm oil mills are still limited. Due to high cellulose contents, it potentially made into various bioproducts, especially as biomaterials. Therefore, a proper extraction technology is needed to obtain a high level of cellulose purity because alkaline treatment can solely remove a part of hemicellulose and lignin. A higher cellulose content can be obtained by further chemical treatments through the bleaching process. However, no information regarding the difference of the isolation performance method to produce cellulose purity by delignification first or vice versa bleaching as an initial stage. The research determined the purity of EFB cellulose with differences in the sequence of bleaching and alkaline delignification stages. The three methods were carried, namely the first method by bleaching using sodium chlorite 3% two times, followed by delignification of NaOH 10% at room temperature, second method with the same conditions but delignification of NaOH 10% at a temperature of 70-80°C and third method by delignification and continued bleaching under the same conditions. The results showed the bleaching method of sodium chlorite of 2 cycles and continued by alkaline delignification (NaOH 10%) at room temperature resulted in higher cellulose purity than other methods. The FTIR test results indicated the detection of the C-O functional group at a wavelength of 1196 cm-1 and the C-H functional group at a wavelength of 2967 cm-1